2020
DOI: 10.1088/1555-6611/abca34
|View full text |Cite
|
Sign up to set email alerts
|

A quantum beat of quantum discord induced by the number of qubits in non-Markovian environments

Abstract: We investigate the protection of the quantum discord of two qubits, individually originated by two generalized amplitude-damping models. Here, each generalized amplitude-damping model consists of N non-interacting qubits interacting with a common zero-temperature reservoir. First, for initial states with extended Werner-like states, we find that the robust quantum discord of two qubits against decoherence can be obtained by controlling the number of qubits in the reserv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Recently, in the [36] An studied entanglement dynamics of two and three atoms in a common environment and found that the disentanglement of atoms can be largely delayed with the increase of the number of non-interacting atoms. Later, the similar idea is applied to the case of initial W state with independent reservoirs [37] (here each subsystem includes the interaction between n qubits and a zero-temperature reservoir called generalized amplitude damping model) for entanglement dynamics, which also has been suggested to protect pairwise entanglement [38][39][40], coherence [41][42][43][44], quantum discord [45] and reduce the entropic uncertainty lower bound [46].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, in the [36] An studied entanglement dynamics of two and three atoms in a common environment and found that the disentanglement of atoms can be largely delayed with the increase of the number of non-interacting atoms. Later, the similar idea is applied to the case of initial W state with independent reservoirs [37] (here each subsystem includes the interaction between n qubits and a zero-temperature reservoir called generalized amplitude damping model) for entanglement dynamics, which also has been suggested to protect pairwise entanglement [38][39][40], coherence [41][42][43][44], quantum discord [45] and reduce the entropic uncertainty lower bound [46].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a generalized amplitude damping model composed of N noninteracting qubits coupled to a common reservoir is suggested to protect entanglement [26][27][28][29][30], coherence [31][32][33][34], quantum discord [35] and the entropic uncertainty lower bound [36]. In this paper, inspired by these studies we try to explore the squeezing property of the generalized amplitude damping model, which has not be seen for similar report up to now.…”
Section: Introductionmentioning
confidence: 99%